2023
DOI: 10.1038/s41420-023-01726-1
|View full text |Cite
|
Sign up to set email alerts
|

RMI1 facilitates repair of ionizing radiation–induced DNA damage and maintenance of genomic stability

Lianying Fang,
Yuxiao Sun,
Mingxin Dong
et al.

Abstract: Ionizing radiation (IR) causes a wide variety of DNA lesions, of which DNA double-stranded breaks (DSBs) are the most deleterious. Homologous recombination (HR) is a crucial route responsible for repairing DSBs. RecQ-mediated genome instability protein 1 (RMI1) is a member of an evolutionarily conserved Bloom syndrome complex, which prevents and resolves aberrant recombination products during HR, thereby promoting genome stability. However, little is known about the role of RMI1 in regulating the cellular resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…ZNF740 is a transcriptional regulator whose DNA binding motifs are associated with enhancer usage in heart failure suggesting that this gene may indeed play a role in cardiotoxicity [ 61 ]. RMI1 facilitates double-stranded break repair and heterodimerizes with TOP3A that has topoisomerase activity in both mitochondria and the nucleus, again suggesting a mechanism behind the association [ 62 , 63 ]. From the adult AC-induced cardiotoxicity GWAS study, our analysis revealed strong effects on the expression of genes including PELI2 and LGALS3 .…”
Section: Discussionmentioning
confidence: 99%
“…ZNF740 is a transcriptional regulator whose DNA binding motifs are associated with enhancer usage in heart failure suggesting that this gene may indeed play a role in cardiotoxicity [ 61 ]. RMI1 facilitates double-stranded break repair and heterodimerizes with TOP3A that has topoisomerase activity in both mitochondria and the nucleus, again suggesting a mechanism behind the association [ 62 , 63 ]. From the adult AC-induced cardiotoxicity GWAS study, our analysis revealed strong effects on the expression of genes including PELI2 and LGALS3 .…”
Section: Discussionmentioning
confidence: 99%